Comparative analysis of Staphylococcus aureus strains by molecular microbiology methods - Peles, Ferenc; Wagner, Martin; Keresztúri, Péter; Béri, Béla; Szabó, András (Acta Agraria Debreceniensis, 2007)
Staphylococcus aureus is a very important pathogen for dairy farms and milk processing plants. Subclinical mastitis is often caused by this species, and it can contaminate bulk tank milk when milking cows are suffering from mastitis. Additionally, thermostable enterotoxins (SE) produced by some types of this bacterium can cause food poisoning.The aim of our research was to examine the number of S. aureus in bulk tank milk in two dairy farms and the enterotoxin-producing ability, genetic relation (pulsotype) and antibiotic resistance of S. aureus strains from different sources (bulk tank milk, udder quarter milk and environment).The results show that the mean number of S. aureus of bulk tank milk of two farms significantly differed (P